O‘QUVCHILARNI KASB-HUNARGA YO‘NALTIRISH OMILLARI, MEXANIZMLARI VA JIHATLARNING IJTIMOIY-PSIXOLOGIK TAHLILI - Yuldasheva, N.K. (SCIENCE and SOCIETY, 2024)
In this article, the psychological scientific analysis of the results are covered the socio-psychological questionnaire to determine the factors and mechanisms of students’ interest, ability, inclination to the profession and their application in practice.